2016
DOI: 10.1017/s0144686x16001136
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong learning in active ageing discourse: its conserving effect on wellbeing, health and vulnerability

Abstract: The Active Ageing Framework has been adapted as a global strategy in ageing policies, practices and research over the last decade. Lifelong learning, however, has not been fully integrated into this discourse. Using survey data provided by 416 adults (aged 60 years and above) enrolled in non-formal general-interest courses in a public continuing education programme in Canada, this study examined the association between older adults’ duration of participation in the courses and their level of psychological well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 48 publications
(106 reference statements)
2
73
0
5
Order By: Relevance
“…Diaz-Orueta et al, 2012). As Narushima et al (2018) point out, continuous participation in life-long learning courses, such as foreign language courses, can develop social cohesion and improve the sense of community participation, which may lead to improved social performance and enhanced well-being. Pot et al (2018) expand that it is partly through the stimulation of social well-being that the cognitive effects of FLL might be observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diaz-Orueta et al, 2012). As Narushima et al (2018) point out, continuous participation in life-long learning courses, such as foreign language courses, can develop social cohesion and improve the sense of community participation, which may lead to improved social performance and enhanced well-being. Pot et al (2018) expand that it is partly through the stimulation of social well-being that the cognitive effects of FLL might be observed.…”
Section: Discussionmentioning
confidence: 99%
“…• Descriptive studies (Panitsides, 2014); studies not focusing on the research topic, including the studies on bilingualism (Small et al, 1999;Friebe and Schmidt-Heartha, 2013;Clare et al, 2014;Zahodne et al, 2014;Narushima et al, 2018); studies having different age of the subjects (Schlegel et al, 2012;Bak et al, 2016;Ghazi-Saidi and Ansaldo, 2017); and review studies (Antoniou et al, 2013;Klimova, 2018) were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on older adults in non-formal general interest programmes find that engagement in learning facilitates knowledge-related, psychological, and social resources that foster the well-being of participants, even or especially for vulnerable groups (Åberg, 2016;Hammond, 2004). High vulnerability, which is more likely in old age, might be compensated by continuously engaging in lifelong learning (Leung & Liu, 2011;Narushima, Liu & Diestelkamp, 2018).…”
Section: Research With Secondary Data On Non-monetary Returns Of Educmentioning
confidence: 99%
“…One way to relieve (or ease) the pressure on the welfare system may, for example, be participation in popular adult education (non-degree further educationso-called 'Folk education') and other adult education systems. These education systems offer meaningful activities for seniors and have been shown to be a way in which senior citizens can be included in society (hence 'inclusion'), experience meaningfulness, and create the conditions for their own well-being (Andersson, Bernerstedt, Forsmark, Rydenstam, & Åberg, 2014;Andersson & Tösse, 2013;Dahlgren & Whitehead, 1991;Hughes & Adriaanse, 2017;Jenkins & Mostafa, 2015;Merriam & Kee, 2014;Mestheneos & Withnall, 2016;Narushima, Liu, & Diestelkamp, 2018). Studies have also indicated certain positive physical and psychological benefits that are experienced by seniors who participate in learning activities (Formosa, 2019;Sabeti, 2017).…”
Section: Introductionmentioning
confidence: 99%